Charter Schools and Students With Disabilities: Legal and Practice Considerations. (March 2018) - Dunn, Michelle E.; Katsiyannis, Antonis; Ryan, Joseph B.
As of the 2013–2014 school year, about 2.5 million school-age students attended charter schools nationwide. Because charter schools are publicly funded entities, they are required to adhere to all federal nondiscriminatory laws as well as the Individuals With Disabilities Education Act. This legal brief provides an overview of charter schools, legal requirements associated with students with disabilities enrolled in charter schools, and recommendations for practice.